Construction of Hierarchical NiCo2O4@NiFe‐LDH Core‐Shell Heterostructure for High‐performance Positive Electrode for Supercapacitor. Issue 7 (9th June 2022) - Luo, Dapeng; Yong, Yi; Hou, Jiang; Guo, Weiguang; Liu, Hengbo; Zhao, Xue; Xiang, Jingrong; ZongZong, Nima; Han, Yuqi; Yan, Minglei
Abstract: In this work, the hierarchical NiCo2 O4 @NiFe‐layered double hydroxide (NiCo2 O4 @NiFe‐LDH) heterostructure has been successfully synthesized by sequential hydrothermal method, heat treatment and electrodeposition, which is investigated as high‐performance positive electrode for supercapacitor. In this unique structure, on the one hand, the NiCo2 O4 as the scaffold provide high conductivity, which accelerates the electron transfer. On other hand, the NiFe‐LDH nanosheets increase the surface area, which offers abundant active sites for electrochemical reaction. Furthermore, the three‐dimensional (3D) hierarchical structures are beneficial to the diffusion for electrolyte ions. Hence, the synergistic effect between NiCo2 O4 and NiFe‐LDH endows the optimal NiCo2 O4 @NiFe‐LDH‐150/CC with excellent electrochemical performance, such as high areal specific capacitance (1.09 F cm −2 @1 mA cm −2 ), small charge‐transfer resistance (0.35 Ω) and superior cycling stability. This study demonstrates the NiCo2 O4 @NiFe‐LDH core‐shell heterostructures are promising positive electrode material for supercapacitors. Abstract : Hierarchical NiCo2 O4 @NiFe‐LDH heterostructure has been successfully synthesized by sequential hydrothermal method, heat treatment and electrodeposition, which is investigated as high‐performance positive electrode for supercapacitor. In this unique structure, the NiCo2 O4 provide high conductivity and the NiFe‐LDH nanosheets offers abundant active sites.